Available Rights of Persons with Disabilities from Their Mothers' Perspectives in Zagazig City - Gamalat M. Abd El-Ghany; Maha M. Abdelaziz (Evidence-Based Nursing Research)
Background: The Convention on the Rights of Persons with Disabilities (CRPD) has a profound influence on disability law and human rights law globally.